Kerja jarak jauh dan produktivitas karyawan: Mengevaluasi dampak jangka panjang dari telecommuting pasca Covid-19 - Sumarno, Sumarno; Karsim, Karsim; Dwiyanto, Dwiyanto; Ekobelawati, Fransiska; Christian, Ferdinandus (Journal of Management and Digital Business, 2024)
This study evaluates the long-term impact of telecommuting post-COVID-19 on employee productivity. With the increased adoption of telecommuting during the pandemic, companies worldwide have transformed work models, necessitating an assessment of this approach’s sustainability. The study employs a literature review method, analyzing 74 articles published between 2020-2024. The study focuses on understanding the influence of telecommuting on productivity, employee well-being, and performance management strategies. The findings reveal that telecommuting offers benefits such as flexible working hours, improved work-life balance, and enhanced efficiency, particularly with adequate technological support. However, challenges such as limited communication, social isolation, and technostress pose significant barriers. To maximize the advantages of telecommuting, organizations need to provide proper technological infrastructure, training, and effective communication policies. A hybrid work model is recommended as a more flexible and inclusive approach to boost productivity while maintaining employee well-being. Telecommuting has the potential to become an integral part of modern, sustainable work strategies if managed with appropriate and adaptive policies that address employees’ needs.